2019
DOI: 10.1101/732800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Osteocalcin-deficient mouse strain without endocrine abnormalities

Abstract: Osteocalcin (OCN), the most abundant non-collagenous protein in the bone matrix, is reported to be a bone-derived endocrine hormone with wide-ranging effects on many aspects of physiology, including glucose metabolism and male fertility. Many of these observations were made using an OCN-deficient mouse allele (Osc -) in which the 2 OCN-encoding genes in mice, Bglap and Bglap2, were deleted in ES cells by homologous recombination. Here we describe mice with a new Bglap and Bglap2 double knockout (dko) allele (B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 42 publications
0
23
1
Order By: Relevance
“…Although the treatment capacity of OCN in neurodegenerative disorders remains to be elucidated [ 340 ], models of movement disorders such as PD demonstrated a neuroprotective effect of OCN [ 341 ], while OCN was reported to improve insulin sensitivity and muscle strength [ 342 ]. Interestingly, the hormonal role of osteocalcin was currently challenged by two individually performed experimental studies [ 343 , 344 ] that generated novel murine osteocalcin-knockout strains which lacked the previously postulated endocrine dysregulation. Therefore, both OCN-deficient mice strains with a Bglap / Bglap2 double-knockout allele displayed regular bone quantity, glucose metabolism, fertility [ 343 ] and muscle mass [ 344 ].…”
Section: Molecular Bases Of Brain-bone Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the treatment capacity of OCN in neurodegenerative disorders remains to be elucidated [ 340 ], models of movement disorders such as PD demonstrated a neuroprotective effect of OCN [ 341 ], while OCN was reported to improve insulin sensitivity and muscle strength [ 342 ]. Interestingly, the hormonal role of osteocalcin was currently challenged by two individually performed experimental studies [ 343 , 344 ] that generated novel murine osteocalcin-knockout strains which lacked the previously postulated endocrine dysregulation. Therefore, both OCN-deficient mice strains with a Bglap / Bglap2 double-knockout allele displayed regular bone quantity, glucose metabolism, fertility [ 343 ] and muscle mass [ 344 ].…”
Section: Molecular Bases Of Brain-bone Crosstalkmentioning
confidence: 99%
“…Interestingly, the hormonal role of osteocalcin was currently challenged by two individually performed experimental studies [ 343 , 344 ] that generated novel murine osteocalcin-knockout strains which lacked the previously postulated endocrine dysregulation. Therefore, both OCN-deficient mice strains with a Bglap / Bglap2 double-knockout allele displayed regular bone quantity, glucose metabolism, fertility [ 343 ] and muscle mass [ 344 ]. Bone microstructure analyses of the two studies revealed an increase in cortical bone carbonate-to-phosphate ratio and collagen maturity [ 343 ] but also the disruption of the biological apatite crystallographic orientation which resulted in reduced bone strength [ 344 ].…”
Section: Molecular Bases Of Brain-bone Crosstalkmentioning
confidence: 99%
“…We were unable to identify changes in secreted factors from osteoblasts and/or osteocytes that explained the phenotype of HSD2 OB/OCY -tg mice. Mice deficient in osteocalcin, an osteoblast-derived secreted molecule, have increased adiposity and glycaemia compared to wild-type mice [ 16 ], although this finding has been recently challenged [ 45 , 46 ]. We observed differences in carboxylated osteocalcin concentrations between wild-type and HSD2 OB/OCY -tg mice, but only at 3 months of age; this is consistent with previous reports of impaired mineralisation in HSD2 OB/OCY -tg mice [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin influences glucose metabolism by stimulating insulin secretion, but it does not regulate appetite or energy expenditure directly [ 35 ]. Although osteocalcin-deficient mice were initially reported to have increased visceral adiposity compared to wild-type mice [ 16 ], recent studies have not found any effect of deleting osteocalcin on regional adiposity [ 45 ] or body weight [ 45 , 46 ]. The contribution of osteocalcin to energy homeostasis is therefore unclear at present.…”
Section: Discussionmentioning
confidence: 99%
“…This milestone paper not only proved that OC plays an important role in energy and glucose homeostasis but also—for the first time—showed that a hormone produced by bone regulates physiological processes not directly linked with bone maintenance. While two recent studies showed no metabolic abnormalities in mice with osteocalcin deficiency (Diegel et.al 2020 Plos Genetics & Moriishi et.al 2020 Plos Genetics), these discrepancies could be attributed to differences in genetic modification methods, mouse genetic backgrounds or housing environments [ 164 , 165 ]. Nonetheless, strong evidence suggested that ucOC exerted its metabolic effects by targeting multiple tissues essential for glucose and lipid metabolism.…”
Section: Chronic Inflammation During the Development Of Type 2 Diabetmentioning
confidence: 99%